Malawi : Staff Report for the 2000 Article IV Consultation and Request for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility. (IMF Staff Country Reports; Country Report ;, 2001)
Although Malawi showed good economic performance under the Poverty Reduction and Growth Facility Arrangement, its poverty rate remained high. Executive Directors stressed the need to improve fiscal and monetary stances, and accelerate structural reforms. They appreciated the 10-point plan to improve budget management, and emphasized the need to sustain the soundness of the banking system. Directors agreed for further concessional assistance and urged the authorities to sustain efforts to improve data collection and dissemination, particularly in the area of fiscal statistics.